Letter : International Brigade Association - Woods, Fred C.
034-0049-001 Registered Office: 70 ST. GEORGES SQUARE, LONDON, S.W.1 CLERICAL & ADMINISTRATIVE WORKERS' UNION Incorporating the National Union of Clerks & Administrative Workers and the Association of Women Clerks & Secretaries Trade Union No. 916 Approved Society No 184 Tel. No. Maryhill 1612 (2 lines) Grams "Uniclerkos. Glasgow" 30 CLOUSTON STREET. GLASGOW. N.W. General Secretary FRED C. WOODS Asst. General Secretary B. Anne Godwin Our ref. A.50/41. Your ref. FCW ILW Sir Walter Citrine, K.B.E., Trades Union Congress, Transport House, Smith Square, LONDON, S.W.1 18th November, 1941, Dear Sir Walter, International Brigade Association. We have recently received a request from one of our Branches for action to assist in a move for the release of the interned members of the International Brigade at present in Vichy France. My General Council would be interested to hear whether it is possible to take any steps through the Trades Union Congress with this object in view. Yours sincerely, Fred C. Woods General Secretary. Please write a separate letter for each subject dealt with 292/946/34/49